Professional Zakat Management Accountability At The National Zakat Amil Agency - Indriana, Indriana; Fikri, Mursyid; Amir, Muhammad (Jurnal Ar-Ribh, 2022)
This study aims to provide an overview of the implementation of professional zakat of the BAZNAS Central Java and conducted an analysis of the accountability of the management of the zakat fund. So reference could be made to an appropriate policy for baznas in Indonesia. In this research is a type of field research (field research) by applying a case study method approach, which examines the accountability of management and implementation of the collection of zakat funds in the Central Java BAZNAS profession. Data collection techniques in this study used the method of documentation and in-depth interviews. The analysis uses the miles and Huberman model methods, namely data reduction, data models, drawing conclusions/verification. The results of this study indicate that: 1) Implementation of Professional Zakat collection which was built by BAZNAS Central Java in strengthening and increasing the potential for collecting Zakat infaq and alms namely by structured and systematic organizing strategy, having a clear and structured collaboration flow, using a transparent information system as a publication media and controlling the use of Zakat funds, Establish a network together with all stakeholders and policy makers to increase the tithe awareness of the muzakki and reduce the risk of losing the trust of muzakki. 2) Accountability practices have been carried out by BAZNAS Central Java as a form of accountability for the use of public funds can be seen from the fulfillment of various dimensions of accountability that are in accordance with the applied SOP.